COVID-19: Smoking cessation and the science of dissemination and implementation in dental care (2020)
Tobacco use was officially identified as an addiction therefore emerged as a policy focus through pulmonology medicine and epidemiology rather than psychiatry. Currently, evidence demonstrates patients with history of smoking and COVID-19 are 14 times more at risk to progress to pneumonia. Since the latest epidemics have involved different problems related to respiratory diseases, the creation and re-evaluation of the designs of programs for the use of tobacco and electronic cigarettes are mandatory in dental schools. An important tool to develop those programs is the Dissemination and Implementation science.